Impact of Vitamin D Replacement on fibrosis score in Chronic Liver Disease patients - Wanichagool, Dhanusorn (Journal of Preventive Medicine Association of Thailand, 2023)
Vitamin D insufficiency and deficiency are prevalent in almost half the healthy population of developed countries, remains a major health concern in the Thai population. According to the 2018 national health database, the prevalence of vitamin D deficiency is approximately 45.2% of total population while the population from middle part of Thailand can be as high as 48.1%. Typically, Vitamin D synthesized from skin and from dietary sources may be stored in the adipocytes, or it may undergo hepatic 25-hydroxylation, which produce 25-hydroxyvitamin D [25(OH)D] or calcidiol. 25(OH)D is hydroxylated in the kidney by 1α-hydroxylase that form active metabolite of vitamin D. Several studies have reported that vitamin D deficiency is associated with multiple liver diseases including hepatic steatosis, hepatitis, liver fibrosis, cirrhosis and hepatocellular carcinoma. Thus far, there is no definitive evidence indicating that vitamin D deficiency is associated with chronic liver disease. This study aims to investigate the impact of vitamin D deficiency on liver fibrosis score in patients with chronic liver disease in Phra Nakhon Si Ayutthaya Hospital. Methods: Patients with chronic liver disease from 2019 to 2021, who had vitamin D deficiency (36 cases) were recruited from the outpatient clinic. Supplemental vitamin D in the form of vitamin D2 (calciferol) 2 tablets/weeks for 12 weeks (20,000 IU/tablet) were given to all patients. Liver fibrosis score i.e. aspartate aminotransferase (AST) to Platelet ratio index (APRI), AST/ALT ratio, the FIB-4 score, model for end-stage liver disease (MELD score were evaluated before and after vitamin D supplement. Mortality rate and liver-related complication was also observed. Results: The common cause of chronic liver disease in our patient was due to chronic hepatitis B virus. Mean vitamin D levels were 22.78±4.64 nanograms per milliliter, AST and ALT were mildly elevated (39.79±20.82 U/L and 32.62±21.98 U/L, respectively), Liver fibrosis score in term of APRI, AST/ALT ratio, FIB-4 score, and MELD score in most of the patients showed absent to mild fibrosis. Eleven patients (31.43%) had shown cirrhotic liver by fibrosis scoring system. After vitamin D supplement, fibrotic score evaluate by mean APRI score increase 0.15± 0.97 U/L (P-value =0.361), The mean FIB-4 score increase 0.51 ± 3.08 (P-value = 0.340) and MELD score decrease (7.30 ± 1.64, P-value =0.268). In group of hepatitis B liver disease patient, APRI, AST /ALT ratio, and FIB-4 score show no significant difference before or after vitamin D supplement. No clinical complication from chronic liver disease, such as portal hypertension, esophageal varices, ascites, cirrhosis, renal failure, or adverse effects from vitamin D supplements, were observed. Summary: Our study shown that vitamin D supplement in chronic liver disease patient with vitamin d insufficient is not associated with improvement of liver fibrosis score. The benefit of vitamin D supplement in patients with chronic liver disease remains unclear.